Unveiling electronic and magnetic properties of Cu3(SeO3)2Cl2 and Cu3(TeO3)2Br2 oxohalide systems via first-principles calculations. (13th December 2021) - Lafargue-Dit-Hauret, William; Rocquefelte, Xavier
Abstract: Here, we report a theoretical investigation of the electronic and magnetic properties of two oxohalide compounds, namely Cu3 (SeO3 )2 Cl2 and Cu3 (TeO3 )2 Br2, using density functional theory (DFT). These layered systems are characterized by two inequivalent Cu sites, with CuO4 and CuO4 X ( X = Cl, Br) environments, respectively. A new magnetic model is proposed through the calculation of the magnetic exchange couplings. Our study discloses the participation of the Se and Te lone-pairs to the long-range magnetic order, providing potential key informations for future chemical design of original magnetic systems.